Semi-mobile rudimentary tissues attached to a congenital intramitral ring in a woman with previous history of embolic stroke: A rare case report. (August 2019) - Nabati, Maryam; Parsaee, Homa; Fattahian, Alireza
Isolated congenital mitral ring is a very rare subtype of congenital mitral valve malformation, which accounts for about one-third of congenital cardiac anomalies associated with left ventricular inflow obstruction. A mitral ring may be easily missed unless the disease is suspected. The mitral valve repair should be considered in symptomatic patients with mitral stenosis. We report a rare case of a 43-year-old woman with an intramitral ring who experienced previous embolic stroke with left hemiplegia. However, stroke happened several years ago and it does not completely prove causality.